Developing the Freezing of Gait Severity Tool: A Delphi consensus study to determine the content of a clinician-rated assessment for freezing of gait severity. (December 2022) - Scully, Aileen E; de Oliveira, Beatriz IR; Hill, Keith D; Tan, Dawn; Pua, Yong Hao; Clark, Ross; Burton, Elissa
Objectives: There is no standardisation of tasks or measures for evaluation of freezing of gait severity in people with Parkinson's disease. This study aimed to develop a clinician-rated tool for freezing of gait severity (i.e. Freezing of Gait Severity Tool), through determining clinicians' ratings of the most important triggering circumstances to be examined and aspects of freezing of gait to be measured. Design: A three-round, web-based Delphi study. Participants: Healthcare professionals, with at least five years' experience in managing freezing of gait in people with Parkinson. Main outcome measures: Round 1 required participants ( n   =  28) to rate items on a 5-point Likert scale, based on priority for inclusion in the Freezing of Gait Severity Tool. In Round 2, participants ( n   =  18) ranked the items based on priority for inclusion. In Round 3, participants ( n   =  18) confirmed or rejected the shortlisted items by judging their ability, on a binary scale, to screen for freezing of gait, detect changes in freezing severity, and discriminate between degrees of severity. Results: Participants agreed with the triggering circumstances of turning hesitation, narrow space hesitation, start hesitation, cognitive dual-tasking, and open space hesitation should be assessed; and the aspects of gait freezing to be measured included freezing type, number of freezing episodes during a task, and average duration of freezing episodes. Conclusions: This study attained a consensus for the items to be included in a clinician-rated tool for freezing of gait severity. Future studies should investigate psychometric properties and clinical feasibility of the Freezing of Gait Severity Tool.